Cine-scapes KOECK. - Koeck, Richard (Taylor and Francis, 2012)
Cine-scapes explores the relationship between urban space, architecture and the moving image. While an impressive amount of research has been done with regards to the way in which architecture is portrayed in film, this book offers a new perspective ... What happens if we begin to see the city as a place for an embodied visual consumption; a visual apparatus or, perhaps, a system that is based on movement, light and the body, and which we can explore in kinematic, kinetic, and kinaesthetic ways?Using film as a lens through which we look at urban spaces and places, Richard Koeck reveals the film.